2021
DOI: 10.7759/cureus.20244
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Psychiatric Comorbidity and Pharmacologic Treatment Patterns Among Patients With Neurofibromatosis Type 1

Abstract: Background and objectiveNeurofibromatosis 1 (NF1) is a genetic disorder that is accompanied by psychiatric comorbidities such as depression, anxiety, and attention-deficit hyperactivity disorder (ADHD) in more than half of the patients. However, there are limited data describing optimal treatment strategies for these conditions. This study aimed to address that gap in understanding and explore the neurobiological basis of psychiatric comorbidities in NF1. Materials and methodsA retrospective cohort study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In adult patients with neurofibromatosis, 46.5% were found to have at least one psychiatric comorbid diagnosis, most commonly mood disorders and anxiety disorders, as opposed to 20% of the general population [13]. NF1 is a complex and multisystem neurocutaneous disorder that can cause neuronal disturbances, leading to psychosis, which can be expressed through auditory and visual hallucinations [14].…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients with neurofibromatosis, 46.5% were found to have at least one psychiatric comorbid diagnosis, most commonly mood disorders and anxiety disorders, as opposed to 20% of the general population [13]. NF1 is a complex and multisystem neurocutaneous disorder that can cause neuronal disturbances, leading to psychosis, which can be expressed through auditory and visual hallucinations [14].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of the QoL and emotional status of NF1 individuals is a critical unmet need. Several articles have shown a clear benefit for NF1 individuals to perform face-to-face [39] or online [40] mind-bodybased interventions which can be associated or not with pharmacological treatments [41] to improve their emotional status and QoL. Recently, a Relaxation Response Resiliency Program (3RP-NF) including mindfulness, copying, and optimism interventions has shown a durable improvement in QoL among adults with NF1 [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Although efficacy of adjunctive VNS therapy in refractory epilepsy has been well documented, only 8.0% of patients achieve seizure freedom (10), which is the case with our patient. Furthermore, it has been shown that VNS has a positive effect on depressive symptoms in patients with epilepsy (11) and that could provide a second-ary benefit of its utility in neurofibromatosis, considering that depression is a frequent comorbidity in these patients (12).…”
Section: Discussionmentioning
confidence: 99%